Rachid Boudjedra's Representations of Terrorism: Le vainqueur de coupe and La Vie à l'endroit - Lynne D. Rogers (Studies in 20th & 21st Century Literature, 2001)
Contemporary fiction either idealizes or demonizes the terrorist as a cultural figure of collective values. In his two contemporary novels, Le vainqueur de coupe and La vie à l'endroit, Rachid Boudjedra, an Algerian novelist, renders two very distinct narratives although both center around terrorist activity and a major sporting event. The first novel is a sympathetic portrait of a young Algerian who gives up his studies to become part of L'Organization. Sentenced to life imprisonment, the young man becomes an international hero. Le vainqueur de coupe offers an explanation for understanding terrorism. In the second novel, La Vie à I'endroit, written sixteen years later, Boudjedra describes the horrors of living under a reign of terrorism for a man similar to himself and his lover, an European doctor. The striking discrepancy in the posture taken towards terrorism in the two novels reveals the need for a closer look at the social complexities and human ethics involved in today's violence and the romanticization of the terrorist as a literary hero. While the first novel makes a compassionate plea for humanizing the terrorist, the second novel witnesses the deadly aftermath of political self-righteousness rooted in past victimization.
Keywords: Rachid Boudjedra; terrorism; fiction; contemporary fiction; collective values; Algerian literature; Le vainqueur de coupe; La vie à l' endroit; violence